Nanoparticles-Based Strategies to Improve the Delivery of Therapeutic Small Interfering RNA in Precision Oncology - Huang, Jinxing; Xiao, Kai (Pharmaceutics, 2022)
Small interfering RNA (siRNA) can selectively suppress the expression of disease-causing genes, holding great promise in the treatment of human diseases, including malignant cancers. In recent years, with the development of chemical modification and delivery technology, several siRNA-based therapeutic drugs have been approved for the treatment of non-cancerous liver diseases. Nevertheless, the clinical development of siRNA-based cancer therapeutics remains a major translational challenge. The main obstacles of siRNA therapeutics in oncology include both extracellular and intracellular barriers, such as instability under physiological conditions, insufficient tumor targeting and permeability (particularly for extrahepatic tumors), off-target effects, poor cellular uptake, and inefficient endosomal escape. The development of clinically suitable and effective siRNA delivery systems is expected to overcome these challenges. Herein, we mainly discuss recent strategies to improve the delivery and efficacy of therapeutic siRNA in cancer, including the application of non-viral nanoparticle-based carriers, the selection of target genes for therapeutic silencing, and the combination with other therapeutic modalities. In addition, we also provide an outlook on the ongoing challenges and possible future developments of siRNA-based cancer therapeutics during clinical translation.